Information technology for teaching and learning in a multi-campus public nursing college - Gopolang Gause; Isaac O. Mokgaola; Mahlasela A. Rakhudu (AOSIS, 2022)
Background: Technologies, such as the use of information technology for teaching and learning, e-learning and virtual learning, are commonly used terms in today's education system. These ever growing and developing modes of teaching and learning have changed the landscape of higher education, in general. As a result, nursing education has equally responded positively to the use of information technology for teaching and learning. Aim: The aim of this study was to describe and compare the readiness to use information technology for teaching and learning for both nursing students and nurse educators in the two campuses of a North West public nursing college. Setting: The study was conducted in a multi-campus North West public nursing college in South Africa. Methods: A quantitative approach of a comparative descriptive design was followed in this study. Descriptive statistics was analysed using the Statistical Package for the Social Sciences (SPSS) Version 27. Results: A total of 285 (254 nursing students and 31 nurse educators) respondents completed the online questionnaires. Both nurse educators and nursing students were in agreement with the information technology use readiness construct (83.9% and 77.9%, respectively). For all the variables with significant ( 0.05) p-values from the Mann-Whitney U test, the mean ranks were higher for the Ngaka Modiri Molema District (NMMD) campus. Conclusion: When comparing the two campuses, conclusion can be drawn that the campus at NMDD is more ready to use information technology for teaching and learning than the campus at Dr Kenneth Kauda District. Contribution: The results of this study contribute to the body of knowledge on technology use for teaching and learning in nursing education.